2018
DOI: 10.1002/pat.4263
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of oligo(4‐methoxyphenol) in water and evaluation of its efficiency in stabilization of polypropylene

Abstract: A hindered polyphenol, oligo(4-methoxyphenol), has been first successfully synthesized via a mild biocatalytic pathway using horseradish peroxidase as catalyst in water without any additive.Then the efficiency of oligo(4-methoxyphenol) in stabilization of polypropylene (PP) was evaluated in terms of thermal analysis and accelerated aging test. It was observed that the apparent activation energy for thermal decomposition of PP/oligo(4-methoxyphenol) calculated by Friedman's method is higher than that of virgin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The solid state decomposition kinetics of PANSA doped LDPE blends were investigated by TG-DTG-DTA thermograms. The each of curves were recorded for different heating rates (5,10,15, and 20 ºC min -1 ) (Figure 1). The TG-DTG and DTA curves of all AP n blends showed that degradation occurs mainly in one step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid state decomposition kinetics of PANSA doped LDPE blends were investigated by TG-DTG-DTA thermograms. The each of curves were recorded for different heating rates (5,10,15, and 20 ºC min -1 ) (Figure 1). The TG-DTG and DTA curves of all AP n blends showed that degradation occurs mainly in one step.…”
Section: Resultsmentioning
confidence: 99%
“…Oligo (4methoxyphenol) is a steric hindered and phenolic compound having high molecular mass. [5]. This compound was also found to be an effective antioxidant in polyethylene stabilization.…”
Section: Introductionmentioning
confidence: 95%
“…Spectra were obtained at regular time intervals in the MIR region of 40 0 0-50 0 cm -1 at a resolution of 4 cm -1 (640 scans) and analyzed using OMNIC Spectra software. Onset oxidation temperature (OOT) was measured by differential scanning calorimetry (DSC) on a TA Instruments Q100 according to already reported procedures [32][33][34] . A sample of 2.5 mg was placed in an aluminum pan.…”
Section: General Characterizationmentioning
confidence: 99%